PENGARUH PEMBELAJARAN PjBL TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN AFFECTIVE MATHEMATICS ENGAGEMENT - Sri Rahayuningsih; Nur Asrawati; Rahmat Kamaruddin (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Age has entered a phase where Science, Technology, Engineering, and Mathematics (STEM) are basic disciplines. Mathematics is at the center of many professions, but it is considered difficult and many students dislike it, even closing their desire for a career in science, engineering, and technology. To face the challenges in the STEAM era, affective mathematics engagement (AME) and mathematical creative thinking skills are needed. The purpose of this study was to analyze 1) the effect of PjBL learning on students' affective mathematics engagement (AME); 2) The effect of PjBL on students' mathematical creative thinking abilities. This type of research is a quasi-experimental (Quasy Experiment) with a population of high school students in the city of Makassar (n = 245; male = 170; female = 75). Sampling was done using random sampling technique so that the sample in this study was determined to be 70 people (n = 70; male = 35; female = 35). The results showed that (1) There was an effect of implementing PjBL on students' Affective Mathematics Engagement (AME). This is known from the average score of Affective Mathematics Engagement (AME) of students where the class that is implemented by PjBL is in the good category, while the class that applies conventional learning is in the sufficient category. (2) There is an effect of PjBL application on students' mathematical creative thinking ability. It is known from the difference in the average value of the experimental class and the control class that is equal to 4.903.